Menyiapkan Talenta Digital: Strategi Pengembangan Sumber Daya Manusia dalam Menghadapi Disrupsi AI - Sinta Bella Agustina; Abdul Rahman; Yike Diana Putri; M. Bambang Purwanto (Pusat Riset dan Inovasi Nasional, 2026)
This research aims to analyze human resource (HR) development strategies in dealing with artificial intelligence (AI) disruption and formulate a digital talent development model based on AI readiness. The global world of work is currently undergoing a major transformation due to technological advances, such as AI, automation, and machine learning, which are causing conventional skills to be increasingly replaced by digital systems. The research approach employed is qualitative descriptive, with a phenomenological analysis conducted through in-depth interviews and literature reviews of industry practitioners, educators, and students in the field of digital technology. Data analysis was conducted using the thematic analysis method to identify patterns of strategy, skill gaps, and collaborative roles between education and industry in the development of digital talents. The results indicate that effective human resource development in response to AI disruption must focus on three key aspects: strengthening the lifelong learning ecosystem, implementing reskilling and upskilling based on digital technology, and fostering collaboration among academics, industry, and government through the Triple Helix approach. The skills most needed in the AI era include a combination of digital literacy, data analytics, AI awareness, critical thinking, creativity, and emotional intelligence. In addition, formal education and industrial training must complement each other in creating adaptive, innovative, and competitive human resources. This research strengthens the relevance of Human Capital Theory, Digital Transformation Framework, and Lifelong Learning Concept as a theoretical foundation in designing digital talent development strategies in the era of the Industrial Revolution 5.0.